Fundamentals of entrepreneurship - Sodri Ariffin; Ismail Ab. Wahab; Zarida Hambali (Oxford Fajar Sdn Bhd, 2013)
Fundamentals of Entrepreneurship was the culmination of an effort by the Ministry of Higher Education (MOHE) to improve the subject of 'Asas Pembudayaan Keusahawanan' which is one of the required entrepreneurship modules in the universities. The chapters are written to fulfil the needs of the Malaysian university students and are orientated to local context to make it more relevant and useful, something which is not available in the imported books on the subject. The book consists of four main parts: i. Foundation of entrepreneurship Students will learn the theory of entrepreneurship and related issues especially on the development of entrepreneurship in Malaysia. ii. Business planning Students will learn about creativity and innovation, identification of business opportunities, preparation of business plan and business support system for entrepreneurs in Malaysia. iii. Management of small business Students will learn about the types of registered business entities, human resources management, marketing management, operation management, financial management, ethics, professionalism and social responsibility. iv. Business practicum Students will be guided on how to do a business practicum, the recommended practicum report format, business presentation and assessment guidelines